Does On-Site Adequacy Assessment by Cytotechnologists Improve Results of EUS guided FNA of Solid Pancreaticobiliary Lesions? - Nayar, Manu K; Chatterjee, Suvadip; Wadehra, Viney; Cunningham, Joanne; Leeds, John; Oppong, Kofi (JOP. Journal of the Pancreas, 2013)
Context Rapid onsite adequacy assessment is stated to improve the diagnostic performance of EUS-FNA. Objectives The aim of this study was to establish if the introduction of adequacy assessment performed by a biomedical scientist (cytotechnologist) to an established EUS service improved the diagnostic accuracy of EUS guided FNA of solid pancreaticobiliary lesions. Design and Patients This retrospective study includes all patients with solid pancreaticobiliary lesions who underwent EUS-FNA from April 2009 to September 2010. An in room cytotechnologist was present for 2 out of the 4 weekly EUS lists and therefore there were two groups identified: Group 1, cytotechnologist absent; and Group 2, cytotechnologist present. Results There were 82 patients in Group 1 and 97 patients in Group 2. There was no statistically significant difference in the number of passes (4.1 vs. 4.3), the inadequate aspirate rate (7.3% vs. 5.1%) or the mean size of the lesions (34.7 vs. 32.6 mm) between the groups. The accuracy, sensitivity, specificity, positive predictive value and negative predictive value in Group 1 were 89%, 88%, 100%, 100% and 50% respectively. The results in Group 2 were 91%, 90%, 100%, 100% and 69% respectively. There was no statistically significant difference between the two groups. Conclusions In this study the adequacy assessment performed by a cytotechnologist did not improve the diagnostic accuracy of EUS-FNA. In an established EUS-FNA service with low inadequate aspirate rates, onsite adequacy assessment may not improve results of the test. Image: Royal Victoria Infirmary. Newcastle upon Tyne, United Kingdom.